Pengaruh Fintech Peer to Peer Lending terhadap Produk Domestik Bruto Indonesia - Cindy Alifia Pramaisshella; Ladi Wajuba Perdini Fisabilillah (Jurnal Ekonomika : INDEPENDEN, 2022)
Gross domestic product is an important indicator in knowing the economic condition of a country in a certain period. Increasing the value of GDP is of course the goal of a country to develop its economy by optimizing its resources. This study aims to determine the effect of peer to peer lending on Indonesia's gross domestic product. This study uses a quantitative approach using quarterly time series data from 2018 to 2021 in the form of Indonesian GDP data, and lending data through peer to peer lending. The analysis technique uses simple linear regression with the Ordinary Least Square model. The results showed that peer to peer lending had a positive influence on Indonesia's gross domestic product with an effect of 0.547711 or 55%. These results indicate that the rapid development of lending through fintech peer to peer lending will have a positive impact on Indonesia's gross domestic product.